The Leuven Gymkhana: Transdisciplinary Action Research Questioning Socially Innovative Multi-Actor Collaborations in COVID Times - Medina-García, Clara; Nagarajan, Sharmada; Van den Broeck, Pieter (Frontiers in Sustainable Food Systems, 2022)
Literatures on social innovation, collective agency and multi-actor collaboration stress the importance of action research and joint problematization to research ongoing processes of collaboration and transformation to advance both theory and practice in these fields. In this paper we analyze our experience building a transdisciplinary action research (TAR) trajectory between 2020 and 2021 to investigate socially innovative multi-actor collaborations (IMACs) and urban governance innovation trajectories in the city of Leuven (Belgium). We specifically focus on (1) how we involved a wide array of researchers, stakeholders and practitioners in the TAR trajectory; (2) how we enacted joint problematization and action, ensuring that all facilitative leadership roles were taken care of; (3) the challenges that the specific COVID context posed on TAR and the innovative tools and approaches we took to adapt under such circumstances; and (4) how our TAR contributed to the ongoing IMACs in Leuven. Discussing our experience in relation to issues raised in action research literature, we summarize key dimensions, roles and tasks necessary in TAR to enable facilitative leadership and multi-actor collaboration and successfully drive joint problematization and transformative change. We conclude that our TAR trajectory in Leuven became a case study of IMAC in itself, and so learnings from our TAR directly dialogue with and inform our empirical analysis of the performance of IMACs too. Through this realization and the analysis of our experience, we get to broader question the role of action research and researchers in urban governance innovation.